Data clustering using max-max roughness and its application to cluster patients suspected heart disease - Mohd Amirol Redzuan, Mat Rofi (2012)
Nowadays,there are many technique to clustering large-scale data.One of the technique to clustering data is using the Rough Set Theory.The objective of this paper is to present the process of Data Clustering Using Maximum-Maximum Roughness and its application to cluster patients suspected heart disease. It is based on clustering techniques based on rough set theory name Max-Max Roughness to describes and employed regarding to solve a classification problem of heart disease patients.